1991
DOI: 10.1038/jcbfm.1991.37
|View full text |Cite
|
Sign up to set email alerts
|

Region of Interest Issues: The Relationship between Structure and Function in the Brain

Abstract: The comparison of data sets from individual subjects between imaging modalities is necessary in order to evaluate the normal physiologic responses of the brain or the pathophysiological changes that accompany disease states. Similarly, it is critical to compare data between individuals both within and across imaging modalities. In a collaborative project with a number of university groups, we have developed a system that allows for the within-subject alignment and registration of three-dimensional data sets ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Validation studies using a dedicated brain shaped phantom have shown that the maximum registra tion error was of the order of the PET pixel size (2 mm) for the wide variety of tested configurations. The soft ware is routinely used today in a clinical context by the physiCians of the Service Hospitalier Frt!deric loliot which rely on the identification of external or inter nal landmarks by an expert in anatomy (Bookstein, 1991;Ende et aI., 1991;Lemoine et aI., 1991) or on interactive tools allowing a manual registration based on visual criteria (Pietrzyk et aI., 1990;Evans et aI., 1991;Greitz et aI., 1991), are more satisfac tory but may suffer from lack of reproducibility. Therefore, semiautomatic retrospective methods have been proposed to register 3D medical images containing a relatively rigid portion of the human body.…”
mentioning
confidence: 99%
“…Validation studies using a dedicated brain shaped phantom have shown that the maximum registra tion error was of the order of the PET pixel size (2 mm) for the wide variety of tested configurations. The soft ware is routinely used today in a clinical context by the physiCians of the Service Hospitalier Frt!deric loliot which rely on the identification of external or inter nal landmarks by an expert in anatomy (Bookstein, 1991;Ende et aI., 1991;Lemoine et aI., 1991) or on interactive tools allowing a manual registration based on visual criteria (Pietrzyk et aI., 1990;Evans et aI., 1991;Greitz et aI., 1991), are more satisfac tory but may suffer from lack of reproducibility. Therefore, semiautomatic retrospective methods have been proposed to register 3D medical images containing a relatively rigid portion of the human body.…”
mentioning
confidence: 99%
“…For example, in typical VOI's of cortical grey matter, there is both spill out of grey matter activity within the borders of the region as well as spill in from the activity of nearby grey and white matter. One approach to dealing with this problem is to define regions well within the anatomical borders to avoid the spillover effects on the boundaries [27], [28]. Indeed as was seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) imaging allows detecting physical, chemical, and physiological changes related to metabolism . In dynamic PET studies, a common approach to identify different functional structures is by drawing manually regions‐of‐interest (ROIs) directly on PET images, and extracting the tissue time‐activity curves (TACs) for further analysis . The manual delineation of ROIs is, however, operator dependent, time‐consuming and challenging due to the inability of the operator to integrate the full TACs of the voxels in the evaluation and also due to noise in the PET images .…”
Section: Introductionmentioning
confidence: 99%